PENGELOLAAN SAMPAH PERMUKIMAN BERBASIS MASYARAKAT - Sri Wahyono; Firman L. Sahwan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2002)
Kampung Banjarsari is a model of community based waste management in the Jakarta metropolitan area. It is becoming an example of an environmentally friendly kampung for other communities from different part of the country. What the Banjarsari reached is the results of very tight cooperation between Banjarsari community, UNESCO and Yayasan Kirai and BPPT since 1996. The main activities in Banjarsari are focused on (1) establishment of an environmental committee at the community level, (2) improvement of the waste collection system (sorting of waste), (3) capitalization on waste trough alternative livelihood activities (paper recycling, composting, growing of plants using locally produced compost as fertiliser), (4) greening programmes, and (5) public awareness.